2011
DOI: 10.1063/1.3552919
|View full text |Cite
|
Sign up to set email alerts
|

Optical properties of functionalized GaN nanowires

Abstract: The evolution of the optical properties of GaN nanowires (NWs) with respect to a sequence of surface functionalization processes is reported; from pristine hydroxylated to finally, 3-mercaptopropyltrimethoxysilane (MPTMS) functionalized GaN NWs. Photoluminescence, Raman, stationary, and time-resolved photoluminescence measurements were applied to investigate the GaN NWs with different surface conditions. A documented surface passivation effect of the GaN NWs induced by the MPTMS functionalization is determined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 37 publications
0
11
0
Order By: Relevance
“…55,56 In addition, the PL spectra of both types of samples also demonstrated yellow band emissions (not shown), which are characteristic for the presence of point defect related deep levels in the bandgap in this material. 5,21,57,58 …”
Section: Optical Propertiesmentioning
confidence: 98%
See 2 more Smart Citations
“…55,56 In addition, the PL spectra of both types of samples also demonstrated yellow band emissions (not shown), which are characteristic for the presence of point defect related deep levels in the bandgap in this material. 5,21,57,58 …”
Section: Optical Propertiesmentioning
confidence: 98%
“…The concentration of cysteamine on the sample surface was determined to be low enough to avoid photon adsorption that has been seen with other surface modifications. 21 What does change is the temperature of phosphoric acid required to maximize photoluminescence in the different types of samples. It has been shown that etching increased the photoluminescence as the surface roughness increases the critical angle for photon escape; 13,14 however, there is an upper limit as over etching can produce light scattering and device degradation.…”
Section: Optical Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…In InGaN, one of the most important semiconductor NW systems currently in use, nonradiative Shockley–Read–Hall (SRH) recombination at the surface defect states may arise from the presence of Ga/In dangling bonds, nitrogen vacancies, and/or incorporated oxygen . The presence of surface states may pin the Fermi level at the surface, causing band bending that decreases the density of free electrons toward the surface . Both of these effects significantly reduce the carrier density and, subsequently, the efficiency of the device.…”
Section: Introductionmentioning
confidence: 99%
“…Different techniques have been employed to passivate surface states, including growing large bandgap AlGaN shells and treating the surface with sulfur‐containing compounds, such as (3‐mercaptopropyl)trimethoxysilane or (NH 4 ) 2 S . Very recently, Zhao et al reported the use of octadecylthiol (ODT) to efficiently passivate the surface dangling bonds and weaken the band bending of an InGaN/GaN quantum‐disk (Qdisk)‐in‐nanowire LED, significantly enhancing the steady‐state photoluminescence (PL) efficiency and external quantum efficiency (EQE) .…”
Section: Introductionmentioning
confidence: 99%